Infusing Oral Health Care into Nursing Curriculum: Addressing Preventive Health in Aging and Disability - Joan Earle Hahn; Leah FitzGerald; Young Kee Markham; Paul Glassman; Nancy Guenther (Nursing Research and Practice)
Access to oral health care is essential for promoting and maintaining overall health and well-being, yet oral health disparities exist among vulnerable and underserved populations. While nurses make up the largest portion of the health care work force, educational preparation to address oral health needs of elders and persons with disabilities is limited across nursing curricula. This descriptive study reports on the interdisciplinary development, implementation, and testing of an oral health module that was included and infused into a graduate nursing curriculum in a three-phase plan. Phase 1 includes evaluation of a lecture presented to eight gerontological nurse practitioner (GNP) students. Phase 2 includes evaluation of GNP students’ perceptions of learning, skills, and confidence following a one-time 8-hour practicum infused into 80 required practicum hours. The evaluation data show promise in preparing nurse practitioner students to assess and address preventive oral health needs of persons aging with disabilities such that further infusion and inclusion in a course for nurse practitioners across five specialties will implemented and tested in Phase 3.